Aquaporins of the PIP2 Class Are Required for Efficient Anther Dehiscence in Tobacco - Bots, Marc (American Society of Plant Biologists, 2005)
Several processes during sexual reproduction in higher plants involve the movement of water between cells or tissues. Before flower anthesis, anther and pollen dehydration takes place before the release of mature pollen at dehiscence. Aquaporins represent a class of proteins that mediates the movement of water over cellular membranes. Aquaporins of the plasmamembrane PIP2 family are expressed in tobacco (Nicotiana tabacum) anthers and may therefore be involved in the movement of water in this organ. To gain more insight into the role these proteins may play in this process, we have analyzed their localization using immunolocalizations and generated plants displaying RNA interference of PIP2 aquaporins. Our results indicate that PIP2 protein expression is modulated during anther development. Furthermore, in tobacco PIP2 RNA interference plants, anther dehydration was slower, and dehiscence occurred later when compared with control plants. Together, our results suggest that aquaporins of the PIP2 class are required for efficient anther dehydration prior to dehiscence.